CORRELATION BETWEEN CORRUPTION CRIMES AND THE PARTICIPATION OF CIVIL SERVANTS IN POLITICAL PARTIES - Norcha Satria Adi Nugroho; Eva Achjani Zulfa (Jurnal Meta-Yuridis, 2023)
Law on the Civil Servant regulates the neutrality of civil servants as free from the influence of interference from all groups and political parties. The participation of a civil servant as a member and/or administrator of a political party is one of a reason for imposing disciplinary punishment, i.e., dishonorable dismissal. In 2013 Bantul, it was found a civil servant in the Education Office had become the Chairman of the Branch Leadership Council of the Bulan Bintang Party Branch. Meanwhile, all rights a civil servant receives are paid from the taxes paid by citizens based on the State Revenue and Expenditure Budget. This research is doctrinal research using a conceptual approach. The results of this study indicate that civil servants who are members and/or administrators of political parties meet the elements of corruption because it is detrimental to state finances. A civil servant who wants to participate in a political party, must first apply for dismissal or be threatened with the most severe disciplinary punishment, i.e., dishonorably discharged. Provisions governing threats and punishments are an indication that a person may no longer obtain the inherent rights of civil servant status such as salary and benefits if he wants to participate in a political party. Thus, civil servants who are found to be members and/or administrators should be subject to administrative sanctions not only dishonorably dismissal but also the obligation to compensate for the loss of the state’s finances or economy and imposed with criminal sanctions